Analysis of exit-ply temperature characteristics and their effects on occurrence of exit-ply damages during UD CFRP drilling. (1st January 2020) - Hou, Guoyi; Zhang, Kaifu; Fan, Xintian; Luo, Bin; Cheng, Hui; Yan, Xiaoye; Li, Yuan
Abstract: This paper focuses on the analysis of exit-ply temperature characteristics and the occurrence of exit-damages during drilling of UD CFRP. Different diameter drills are used to reveal their effects on temperature variation, cutting mechanism and damage modes. The results show that exit-ply temperature is strongly dependent on the interaction between tool-workpiece system. In particular, an significant factor to affect the peak temperature is the location of unruptured region when main cutting edges act on exit-plies, which will result in high temperature appearing along hole edge at θ  ~ 0°. The two-dimensional maps of high temperature along borehole edge are drawn at a continuous change of fiber cutting angles, based on which the dependences of exit-damages on the cutting temperature variations are discussed for the first time. The effects of high temperature on the exit-ply hole wall damages are concluded by examining the micrographs. And the width of loose surface near the hole-exit is identified to represent the functioning range of the excessive temperature. Moreover, the effects of high temperature on the exit-delaminations are analyzed by the adjusted delamination factor ( Fda ) at various drilling parameters.